2022
DOI: 10.1213/ane.0000000000005854
|View full text |Cite
|
Sign up to set email alerts
|

The Perioperative Use of Benzodiazepines for Major Orthopedic Surgery in the United States

Abstract: BACKGROUND: Despite numerous indications for perioperative benzodiazepine use, associated risks may be exacerbated in elderly and comorbid patients. In the absence of national utilization data, we aimed to describe utilization patterns using national claims data from total hip/knee arthroplasty patients (THA/TKA), an increasingly older and vulnerable surgical population. METHODS: We included data on 1,863,996 TKAs and 985,471 THAs (Premier Healthcare claims data, 2006–2019). Benzodiazepine utilization (strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Approximately 5% of our study population was identified as Black, which is slightly lower than reported Black patient populations in similar studies including patients with commercial or Medicare Advantage insurance. 10,27 The table presents our primary unadjusted and adjusted models estimating the association between race and regional anesthesia utilization for postoperative pain, along with selected sensitivity analyses. The primary adjusted model was specified as a multivariable logistic regression that accounted for age, sex, elixhauser comorbidities, preoperative opioid, anticoagulant, and antiplatelet utilization, and year and hospital fixed effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 5% of our study population was identified as Black, which is slightly lower than reported Black patient populations in similar studies including patients with commercial or Medicare Advantage insurance. 10,27 The table presents our primary unadjusted and adjusted models estimating the association between race and regional anesthesia utilization for postoperative pain, along with selected sensitivity analyses. The primary adjusted model was specified as a multivariable logistic regression that accounted for age, sex, elixhauser comorbidities, preoperative opioid, anticoagulant, and antiplatelet utilization, and year and hospital fixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5% of our study population was identified as Black, which is slightly lower than reported Black patient populations in similar studies including patients with commercial or Medicare Advantage insurance. 10,27 Given that the Black and White race categories have been validated, it is unlikely that this difference is due to misclassification bias; rather, this difference in the proportion of Black patients potentially stems from varied enrollment patterns of minoritized populations in fee-for-service versus Medicare Advantage ( i.e. , managed care) plans.…”
Section: Discussionmentioning
confidence: 99%
“…The use of benzodiazepines in elderly patients is surprising, given the known risk of benzodiazepine use in the elderly. Benzodiazepine use—regardless of short or long half-life—has been linked to an increased risk of falls, hip fracture, and cognitive impairment; thus, the association with postoperative delirium is of particular importance [ 3 , 8 ]. Indeed, the 2019 edition of the American Geriatrics Society Beers Criteria for Potentially Inappropriate Medication Use in Older Adults recommends that benzodiazepines be avoided in elderly patients [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 Despite this, a majority of older surgical patients in the US receive benzodiazepines during anaesthesia care. 8 , 9 …”
mentioning
confidence: 99%